STRATEGI BERSAING MELALUI KEUNGGULAN PRODUK (RIAU’S CASE) - Widiyanto, Ibnu (Fokus Ekonomi, 2006)
This period is a hypercompetition era where a product advantage is very fast eroded. This is due to the extensive entrance of foreign products to local market and technological development. To survive, a business organization must formulate a proper strategy and keep a close relationship with stakeholders. A proper strategy selection is a fundamental element within this hypercompetition period. A principle of redifferentiation-repositioning and brand equity remodeling is required to be in use in order to maintain product success in a market. This principle deals with consumer satisfaction. Though a global product, a business unit must link its strategy to its served market. To do this, indeed, a product adaptation is frequently required to sustain its advantage. An advantage value is not from the view of revenues (producers) but that of consumers (market driven). A glocalization principle therefore requires a very sound and robust internal business factor. This can be presented by an alliance strategic. Riau, if its product wants to be successful in its served market, must learn from others to avoid similar business failure.Keywords: Redifferentiation-Repositioning, Brand Equity Remodeling, A Glocalization Principle